2018
DOI: 10.1016/j.prosdent.2017.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Fracture load of complete-arch implant-supported prostheses reinforced with nylon-silica mesh: An in vitro study

Abstract: Reinforcement with nylon mesh increased the mean maximum load of implant-supported complete-arch prostheses at both cantilever lengths. The cantilever to the premolar (5 mm) presented the highest maximum load values to fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…The incidence of excessive loads on the cantilever of an implant-supported prosthesis is a factor of extreme importance when the rehabilitation success is under evaluation. Excessive loading can lead to bone loss around the implant and to the prosthesis failure (3,5). In this way, the occlusal contacts must be adjusted so that the force is reduced in the cantilever region and distributed to the implants (6).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of excessive loads on the cantilever of an implant-supported prosthesis is a factor of extreme importance when the rehabilitation success is under evaluation. Excessive loading can lead to bone loss around the implant and to the prosthesis failure (3,5). In this way, the occlusal contacts must be adjusted so that the force is reduced in the cantilever region and distributed to the implants (6).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not always possible to use a definitive prosthesis immediately, requiring the manufacture of a temporary structure to maintain the occlusion and masticatory function in the rehabilitated patient (7). In this sense, acrylic resin complete-arch implant-supported prostheses with provisional abutments provides a straight forward interim restoration with good tissue response (3,7). In a previous study it was demonstrated that incorporating silica-nylon mesh inside the acrylic resin of this prosthesis modality can increase the load bearing capacity during compression, regardless of the cantilever size (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in cases of implant installation to retain and/or give support for complete dentures [6], TAAR present precarious mechanical properties and can frequently fracture [1][2][3]5,[7][8][9][10]. This can occur as a result of occlusal disharmony, overloading, fatigue and impact caused by accidents [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This can occur as a result of occlusal disharmony, overloading, fatigue and impact caused by accidents [11][12]. Specially during the osseointegration phase of a protocol type prosthesis, which usually presents cantilever [13], provisional prosthesis made entirely of TAAR may be used over the implants [6]. Thus, the contraindication for the patient is the reduced longevity of such prosthesis.…”
Section: Introductionmentioning
confidence: 99%